2013
DOI: 10.36076/ppj.2013/16/e199
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanoparticles that Mimic Immune Cells in Pain Control Inducing Analgesic and Anti-inflammatory Actions: A Potential Novel Treatment of Acute and Chronic Pain Conditions

Abstract: Background: The peripheral immune-derived opioid analgesic pathway has been well established as a novel target in the clinical pain management of a number of painful pathologies, including acute inflammatory pain, neuropathic pain, and rheumatoid arthritis. Objective: Our objective was to engineer targeted nanoparticles that mimic immune cells in peripheral pain control to deliver opioids, in particular loperamide HCl, specifically to peripheral opioid receptors to induce analgesic and anti-inflammatory action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 50 publications
0
10
0
5
Order By: Relevance
“…ICAM-1 regulates the homing of opioidproducing cells and the subsequent generation of analgesia within sites of painful inflammation [50]. Loperamide-encapsulated anti-ICAM-1 immunoliposomes exerted analgesic and anti-inflammatory effects exclusively in peripheral painful inflamed tissue [52]. The authors proposed that engineering targeted nanoparticles can be beneficial in treating pain disorders [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAM-1 regulates the homing of opioidproducing cells and the subsequent generation of analgesia within sites of painful inflammation [50]. Loperamide-encapsulated anti-ICAM-1 immunoliposomes exerted analgesic and anti-inflammatory effects exclusively in peripheral painful inflamed tissue [52]. The authors proposed that engineering targeted nanoparticles can be beneficial in treating pain disorders [52].…”
Section: Discussionmentioning
confidence: 99%
“…Loperamide-encapsulated anti-ICAM-1 immunoliposomes exerted analgesic and anti-inflammatory effects exclusively in peripheral painful inflamed tissue [52]. The authors proposed that engineering targeted nanoparticles can be beneficial in treating pain disorders [52]. Exosomes released by monocytes induce ICAM-1 and cytokines via activation of NFκB [53].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that, in early stages of inflammation (6 h after inflammation), both peripheral and central opioid receptors are involved in the antinociceptive effect [21], whereas in later stages (4-6 days after inflammation), endogenous analgesia is mediated exclusively by peripheral opioid and its receptors [19,22]. However, due to the limitations of experimental studies, pharmacological techniques, or other aspects, in peripheral endogenous opioid peptides for treating inflammatory pain, there are still some challenges to recruit more opioid peptide-containing immune cells to the inflammation site and to efficiently promote the release of immune cell-derived opioid peptides and the synthesis of opioid receptors in inflammation site [21,23].…”
Section: Immunocytes Infiltrated In the Inflamed Tissue Express And Release Opioid Peptides Having Significant Analgesic Effects Neutrophmentioning
confidence: 99%
“…To address cancer-induced bone pain, Gdowski et al (2017) modified PLGA with the bone microenvironment targeting amino-bisphosphonate, to deliver cabazitaxel for efficient pain relief in a bone metastatic prostate cancer model. To mimic the endogenous response in inflammatory sites, Hua et al designed opioid loaded liposomes with the capacity to target inflammatory environments and release the corresponding drugs for simultaneous pain relief (Hua and Cabot, 2013). Important research described by Ramírez-García et al (2019) reveals that their novel pH-responsive nanomaterials with the ability to target neurokinin-1 receptors (NK 1 R) in the endosome display excellent capacity for preventing chronic pain.…”
Section: Targeted Nanomaterials For Pain Reliefmentioning
confidence: 99%